Revision of the deep-water cone snail fauna from New Caledonia (Gastropoda, Conoidea) - Manuel J. Tenorio; Nicolas Puillandre (European Journal of Taxonomy, 2023)
The present work reviews the deep-water cone fauna of New Caledonia and its Economic Exclusive Zone. It is based on the material collected for more than 40 years by oceanographic expeditions in the deep waters surrounding New Caledonia, organized by the Muséum national d’histoire naturelle-Paris/ORSTOM, then Institut de Recherche pour le Développement, in the framework of the Tropical Deep-Sea Benthos programme. A total of 2377 lots containing 5113 specimens collected in depths between 100 and 1260 m have been examined. About 770 specimens were collected live, and allowed for radular and DNA studies. A phylogenetic analysis, based on the cox1 gene, of the deep-water cone snail fauna of New Caledonia is presented, along with a detailed, fully illustrated taxonomic account with data on geographic and bathymetric distribution and radular morphology. A total of 76 different species of cone snails were identified among the collected material. Of these, 22 corresponded to typical shallow water species, which were most likely translocated into deeper water, whereas 54 could be considered true components of the deep water (below 100 m) cone snail fauna. Species of the genus Profundiconus represent 22%, whereas those of the genera Conasprella and Conus represent 28% and 50%, respectively. Eleven deep water cone species can be considered as endemic to the New Caledonia EEZ, representing 20.3% of the total. The most abundant species found (more than 400 specimens each) were Conus (Afonsoconus) bruuni, Conasprella (Boucheticonus) alisi, Conasprella (Conasprella) boucheti, and Profundiconus vaubani. The new species Conus (Taranteconus) samadiae sp. nov. is hereby described.